IMPLEMENTATION OF THE CIRCULAR ECONOMY THROUGH COMMUNITY EMPOWERMENT: TRANSFORMING SPENT COFFEE GROUNDS INTO AROMATHERAPY CANDLES AND ROOM FRESHENERS IN JINGKANG VILLAGE - Saufik Luthfianto; M. Fajar Nurwildani; Tofik Hidayat; Siswiyanti Siswiyanti; Rusman Kosasih; Yoma Duta Wijaya; Karisma Lela Noviana (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
Spent coffee grounds are one of the organic wastes that remain underutilized despite their significant potential to be transformed into value-added products. This community service program aimed to enhance the knowledge and practical skills of the residents of Jingkang Village in converting spent coffee grounds into aromatherapy candles and air fresheners based on the principles of the circular economy. The program employed a Participatory Action Research (PAR) approach consisting of problem identification, program planning, training implementation, monitoring and evaluation, and reflection. The activity involved 15 participants, including community members, micro-enterprise actors, and women's community groups. Program effectiveness was evaluated using pre-test and post-test assessments and analysed through a Paired Sample t-test. The results demonstrated that the average participant score increased from 46.70 to 86.00, representing an 84.15% improvement. Statistical analysis confirmed a significant difference between pre-test and post-test scores (p < 0.001). Furthermore, all program success indicators were achieved, including a 100% attendance rate, 100% participant competency in producing the products, a participant satisfaction level of 93.30%, and all products meeting usability standards. The novelty of this program lies in integrating the Participatory Action Research (PAR) approach, circular economy principles, and quantitative statistical evaluation into a community empowerment model utilizing spent coffee grounds as value-added products. This model has strong potential to be replicated in other coffee-producing communities to promote sustainable waste management and local economic development.